Book review Vida e Obra do Comendador Montenegro. Um Lousãnense visionário no Brasil, by Sônia Maria de Freitas [(2013). São Paulo: Polo Printer. ISBN 978-85-65943-31-4 - Witzel de Souza , Bruno Gabriel (Tiempo y economía, 2019)
The book “Vida e Obra do Comendador Montenegro. Um Lousanense visionário no Brasil”, by Prof. Sonia Maria de Freitas, is a biographical account about João Elisário de Carvalho Montenegro. Even if highly praised by his contemporaneous, Montenegro is a relatively less known figure in the Brazilian historiography –except by the more classical studies–, despite his many contributions to technological adoption, contractual innovations in Brazilian labor markets, and active participation in benefit associations. Prof. Freita’s book is thus a welcomed work. It will consolidate as an important reference to scholars interested in the transition from slavery in Brazil; foster research about labor organizations in Latin American plantations; and provide a pleasant reading to a broader audience.